A novel rapid quantitative method reveals stathmin‐1 as a promising marker for esophageal squamous cell carcinoma - Lu Yan; Xiu Dong; Jiajia Gao; Fang Liu; Lanping Zhou; Yulin Sun; Xiaohang Zhao (Cancer Medicine, 2018)
Abstract Stathmin‐1 is a microtubule depolymerization protein that regulates cell division, growth, migration, and invasion. Overexpression of stathmin‐1 has been observed to be associated with metastasis, poor prognosis, and chemoresistance in various human cancers. Our previous studies found that serum stathmin‐1 was significantly elevated in patients with esophageal squamous cell carcinoma (ESCC) by ELISAs. Here, we constructed high‐affinity monoclonal antibodies and then developed a competitive AlphaLISA for rapid, accurate quantitation of stathmin‐1 in serum. Compared to ELISA, our homogeneous AlphaLISA showed better sensitivity and accuracy, a lower limit of detection, and a wider linear range. The measurements of nearly 1000 clinical samples showed that serum stathmin‐1 level increased dramatically in patients with squamous cell carcinoma (SCC), especially in ESCC, with a sensitivity and a specificity of 81% and 94%, respectively. Even for early stage ESCC, stathmin‐1 achieved an area under the receiver operating characteristic curve (AUC) of 0.88. Meanwhile, raised concentrations of stathmin‐1 were associated with lymph node metastasis and advanced cancer stage. Notably, various types of SCC showed significantly higher AUCs in serum stathmin‐1 detection compared to adenocarcinoma. Furthermore, we confirmed that stathmin‐1 was enriched in the oncogenic exosomes, which can explain the reason why it enters into the blood to serve as a tumor surrogate. In conclusion, this large‐scale and systematic study of serum stathmin‐1 measured by our newly established AlphaLISA showed that stathmin‐1 is a very promising diagnostic and predictive marker for SCC in the clinic, especially for ESCC.